A Brief History of "Gaze" - Folkart, Barbara (Université d'Ottawa | University of Ottawa, 2013)
Much contemporary academic writing is characterized by the abnormally high frequency and distinctly unidiomatic collocational range of the word "gaze". This essay sees the root of the phenomenon in translation, more specifically in the canonical translations to which many Anglophone academics owe their acquaintance with the ideas of Sartre, Merleau-Ponty, Foucault and Lacan. Where the word "regard", used fluently and colloquially in the great philosophical texts of the late 20th century, was part of a whole, complex conceptual field, the translators imposed "gaze" as a one-size-fits-all rendering over the entire range of contextual meanings connotations and collocations. In so doing, they set the stage for a protracted process of term-formation. Reified into a rigid designator, "gaze" became an empty signifier, fairly begging to be invested with Deep Meaning. All the unilingual exegetes had to do was read-in whatever signifieds they chose to develop within their various frames of reference. Thus was set in motion an ongoing process of conceptual drift whose outcomes, both trivial and creative, continue to proliferate.
Keywords: translation; register formation; regard-gaze; Sartre, Foucault, Merleau-Ponty, Lacan; conceptual drift